นิเวศวิทยาการสืบพันธุ์และการใช้พื้นที่เกษตรกรรมของนกยูง Pavo muticus Linnaeus, 1766 ที่อุทยานแห่งชาติดอยภูนาง - สิริรักษ์ อารทรากร (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The breeding season of green peafowl is around November to May. The territorial area is at least 0.301 ± 0.073km2. Some parts of territory are overlap. Displaying area is found at plain on fine gravel or dusty area of hill ridge with open canopy during November to May, 3.46 ± 1.84 m2 in average area. Number of displaying area is increase with open area and has negative correlation with canopy cover (rs = -0.991, p < 0.05), ground cover (rs = -0.865, p < 0.05), as well as the abundance of shrub (rs = -0.847, p < 0.05) and herb (rs = -0.883, p < 0.05). Green peafowl nested on hill crack or grassy plain area of dry deciduous forest that have never been fired after December. Young traces are found in March at 2 - 4 young per female. Their brood rearing area is along hill column with high undergrowth, and occasionally found near the male s displaying area. The green peafowl are observed from 39 out of 93 samplings of various agricultural fields. The traces in agricultural field are found during August 2000 to March 2001 which at the same time as com are seeding until plough, black beans are cultivated, peanuts are flowering until harvesting and plough, and the cottons are flowering and after harvesting. The green peafowl did not use the agricultural field when human are present. The preference of green peafowl in agricultural fields are significantly correlated with crop-growth period ({u1D4B3}2 = 31.009, p < 0.05), and crop height ({u1D4B3}2 = 18.720, p < 0.05). The average number of green peafowl and time spending in agricultural field are positive correlation with the arthropod abundance in the forest (rs = 0.829, p < 0.05 and rs = 0.829, p < 0.05, respectively). On the other hand, it has negative correlation with seeding plant abundance (rs = -0.900, p < 0.05 and rs = -0.900, p < 0.05, respectively) and vertebrate abundance in the forest (rs = -0.829, p < 0.05 and rs = -0.886, p < 0.05, respectively). The average temperature in the morning is also correlated with the average number of green peafowl that use the agricultural field in the morning (rs = 0.889, p < 0.05).